(untitled) (Research, Society and Development, 2022)
The study seeks to identify and analyze the view of youth in relation to violence in sport and its implications in sports practiced in the school environment. The specific objectives are: to verify the level of concern of young people from Pedro II College, São Cristóvão III campus, about violence in school sports; analyze which sports are more prone to manifestations of violence, according to these young people; identify, according to Pedro II students, the possible influencing factors of violent attitudes in sport. We use the qualitative approach and in all, 132 young people participated in the work (121 questionnaires and 11 interviews). We use categorization as a method of data analysis. Exaggerated competitiveness, lack of education and lack of emotional control were the most remembered among the factors influencing violent attitudes in sport. Given the data, it is assumed that our civilizing process, based on Elias and Dunning, is not fully established.